SUSTAINABLE FOREST MANAGEMENT PRIORITIES IN A SPECIAL PURPOSE FOREST AREA, TEMANGGUNG - Variantika Metasari; Rahmawaty; Feti Fatimatuzzahroh (Jurnal Belantara, 2026)
The Special Purpose Forest Area of the Indonesian National Counterterrorism Agency (KHDTK BNPT) in Central Java, Indonesia, is a forest area developed for forest rehabilitation, community empowerment, and social rehabilitation, including deradicalization and social reintegration programs for former terrorism convicts through productive forestry activities. However, repeated forest fires, vegetation degradation, and community dependence on land utilization pose challenges to sustainable management. This study aimed to determine sustainable management priorities of KHDTK BNPT using the Analytical Hierarchy Process (AHP). Data were collected through field observations, interviews, literature reviews, and AHP questionnaires involving eight expert respondents. The criteria and management alternatives were developed based on ecological, social, economic, and institutional considerations integrated with the Nature-Based Solutions (NbS) approach. The results showed that institutional and forest management was the highest-priority criterion (0.413), followed by ecology and environment (0.265), Social and Community Dimension (0.163), and Economic Dimension (0.159). The global priority ranking indicated that institutional activity of Forest Farmer Groups (KTH), area security stability, land tenure status, and Vegetation Density were the highest-priority management alternatives. These findings demonstrate that sustainable management of KHDTK BNPT depends on strengthening local institutions, improving governance effectiveness, maintaining ecosystem rehabilitation efforts, and enhancing community participation to support the long-term implementation of Nature-based Solutions (NbS). Therefore, management programs should prioritize strengthening the capacity and involvement of Forest Farmer Groups (KTH), improving area security and land tenure clarity, and maintaining vegetation restoration activities as key actions to support the implementation of Nature-based Solutions (NbS) and sustainable forest management.